GRAPH THEORY IN ACTION SOLVING: REAL-LIFE PROBLEMS WITH PRIM'S AND KRUSKAL ALGORITHMS - Norain binti Ahmad Nordin; Nuramirah binti Juma'at; Norhaliza binti Abu Bakar (2026)
Graphs are all around us, from the roads we navigate to the networks that link us. Graph Theory in Action: Solving Real-Life Problems with Algorithms brings this powerful mathematical tool to life, exploring how graphs and trees optimize real-world systems. This book delves into essential algorithms-Kruskal's and Prim's—and their applications in solving problems like finding the shortest routes, minimizing costs, and optimizing connections. Compiled from case studies by first-year IT diploma students, it showcases practical uses of Minimum Spanning Trees (MST) to tackle real-world challenges. Whether you're a student, educator, or professional in mathematics, computer science, or engineering, this book offers a hands-on understanding of graph theory and its far-reaching impact. Unlock the potential of graph theory and see how it shapes the world we live in!